NATURAL-SCIENCE EDUCATION: SCIENTIFIC AND RELIGIOUS KNOWLEDGE CORRELATION IN THE VIEW OF A SYMMETRY PRINCIPLE. PART I. THE CONTENT OF A SYMMETRY PRINCIPLE - Vitaly L. Gapontsev; Marina G. Gapontseva (Образование и наука)
The aim of the investigation is to disclose the content of a symmetry principle; to show system hierarchy of its forms, developed in the course of evolution of scientific knowledge, a society and development of individual consciousness of the person. Methods. Based on the analysis of existing scientific sources, comparison, synthesis and generalisation of its content, the role of symmetry was found out in the course of historical formation of scientific disciplines, arrangement of an empirical set of the facts and its subsequent registration in the form of strict deductive systems. Results. It is proved that the concept «a symmetry principle» (V. I. Vernadsky was the first to coin this concept into the circulation) objectifies now the highest level of scientific knowledge. Following E. Vigner’s works, it is said that set of forms of symmetry determines structure of scientific knowledge. On the one hand, these forms have got a deep empirical basis and a close connection with figurative perception of the validity; on the other – they have strict mathematical definitions and generate particular principles of symmetry of Mathematics and Physics based on axiomatic constructions of exact disciplines. Stages of formation and development of a number of scientific disciplines such as Mathematics, Physics, Chemistry and Biology are compared; the peculiarities and common features of its evolution are designated. Invariants and corresponding symmetries in formation of individual consciousness of the person are allocated. Scientific novelty. Developing V. I. Vernadsky’s idea, as he used only the short characteristic of a general scientific principle of symmetry, the authors of the present study consider symmetry forms in various branches of knowledge as particular displays of the given principle. Based on the principle of symmetry as a set of symmetry forms, this principle allows the authors to take a fresh look at the decision of methodological problems of a science, in particular problems of a correlation of scientific and religious knowledge, and as a whole – forming of hierarchy of scientific disciplines that will include not only all existing scientific directions from strict deductive to empirical, but even those directions that are not recognised as scientific disciplines. Such possibilities are given by reason of the double logic status of concept «symmetry» – as the general inductive and as primary deductive phenomenon. Practical significance. Research outcomes can be useful and form a basis for optimisation of structure of the educational content – designing of a new throughline of the training providing formation of a complete picture of scientific knowledge. The necessity of such throughline is connected with education crisis in the conditions of continuously growing scope of information and as a result redundancy of curriculums. The disciplines of the general natural-science courses, such as «Natural-science World View» and «Concept of Modern Natural Sciences» can be independent elements of similar training under the condition of selection of its content according to a fundamental principle of symmetry.